Consumers' multifaceted deal knowledge in a grocery retail setting. Issue 1 (1st January 2017) - Jensen, Birger Boutrup; Bech-Larsen, Tino
Abstract: Despite its relevance to retailers, studies of consumers' deal knowledge have been few. This study explores consumers' deal knowledge before, during, and after the store visit applying a between-subjects field-study design with 1204 respondents. In particular, the authors investigate perception of deal price status, typical deal price knowledge, and deal-spotting ability. Results show reasonably stable knowledge of typical deal prices, while knowledge of deal price status and deal-spotting ability improves significantly during grocery shopping. Surprisingly, consumers' deal knowledge is not conditional on purchasing a special thus indicating that most consumers, consciously or unconsciously, scan for promotion signals when shopping groceries. In addition, the results suggest consumers are not easily fooled, as the vast majority is able to spot 'good' and 'bad' deals, while also possessing typical deal price knowledge. Furthermore, the findings suggest that consumers store internal reference deal prices. Retailers are therefore well advised to consider mixed depth and creative discount patterns to prevent 'perfect' perceptions of typical deal prices.